The Effect of Media Marketing Effort, E-Wom on Apartment Purchase Decision with Information Transparency as moderating variable - Isti Okvita Sari; Denpharanto Agung Krisprimandoyo; Teofilus Teofilus; Gracia Ongkowijoyo (UNIVED Press, 2025)
This study investigates the influence of Social Media Marketing Efforts (SMME), Electronic Word of Mouth (E-WOM), and Information Transparency on apartment purchase decisions. Using a quantitative descriptive approach, data were collected from consumers who had purchased apartments at Barsa City Yogyakarta and analyzed through multiple regression and statistical tests in SPSS. The Macro PROCESS tool was employed to test the moderation hypothesis. The results revealed that SMME and E-WOM significantly and positively impact apartment purchase decisions, emphasizing the importance of social media strategies and consumer recommendations in driving purchases. However, the hypothesis regarding the moderating role of Information Transparency was not supported, indicating that the level of transparency does not alter the influence of SMME and E-WOM on purchase decisions. These findings highlight the critical role of social media marketing and E-WOM in shaping consumer behavior in the property sector, while also suggesting that other factors may better explain the role of Information Transparency.